Festas "italianas" em São Paulo e a proteção do patrimônio imaterial: a identidade de grupo no contexto da diversidade - Ferreira Junior, Silvio Pinto (2009)
The register of popular festivals as immaterial heritage, in this dissertation in particular the festivals of Italian origins in the city of Sao Paulo, represents much more than the recognition of the important cultural influence of immigrants. The attempt to reconstruct the history of the festivals Nossa Senhora de Casaluce, Nossa Senhora Achiropita, São Vito, São Francisco de Paola and São Gennaro, permitted to discover other questions that are not limited to the description or recovery of a tradition. In search of the origin of these festivals in Italy, the field of study broadened, providing an analysis of today s much discussed issues like citizenship, identity, diversity and multiculturalism. These issues did not just complete the initial proposition, but opened ways to a more far-reaching discussion than it could have been imagined in the beginning